Accumulation and Transport of Cd, Pb, As, and Cr in Different Maize Varieties in Southwest China - Qi Liu; Sheng Wang; Jijiang Zhou; Li Bao; Wenbing Zhou; Naiming Zhang (Agriculture)
The southwestern region of China is one of the major maize (Zea mays L.)-producing areas and a concentrated zone of farmland contaminated by heavy metals (HMs). Selection of maize varieties with low accumulation of HMs under complex HM pollution conditions is one the most feasible and effective ways for safe utilization of HM-polluted farmland. In this study, we conducted field experiments to investigate the differences in biological traits among 28 local maize varieties under combined soil pollution with Cd, Pb, As, Cr, and Hg. We analyzed the absorption, accumulation, and transport characteristics of Cd, Pb, As, and Cr in various parts of the maize plant (Hg was not detected in any part of maize plants) and explored the relationships of HM contents in different parts of maize with soil HM contents through cluster analysis, correlation analysis, and principal component analysis. The results indicated that among different biological traits of maize, root length, root dry weight, and plant height were the most significantly influenced by soil HM content, while stem dry weight was the least affected. The accumulation capacity of various maize parts for HMs followed the order of grains < stems < cobs < leaves < roots, while the transport capacity followed the order of root–grain < root–stem < cob–grain < stem–cob < stem–leaf. In addition, the accumulation capacity of maize grains for HMs followed the order of As < Cr < Pb < Cd. Different HMs exhibited synergistic effects in various maize parts, except for the stem, particularly in the grains. A synchronous transport mechanism was observed for As and other HMs in different parts. The accumulation of HMs in maize was primarily derived from human activities such as the extraction, storage, and smelting of non-ferrous metals, while the HMs in soil parent material and weathering products played a secondary role. The yield of the tested maize varieties ranged from 7377.6 to 11,037.0 kg·hm−2, with M5 (Haoyu 1511) achieving the highest yield. M2, M4, M5, M9, M10, M21, and M25–28 were identified as suitable varieties with low Cd, Pb, As, and Cr accumulation for popularization in HM-contaminated soils in southwestern China due to their low accumulation of HMs.